High-performance solid-waste-based offshore wind power grouting material and preparation method thereof
By using solid waste-based gelling materials and other high-performance additives, a composite gelling system is formed, which solves the problems of high energy consumption and large carbon displacement of offshore wind power grouting materials, and achieves high-strength, low shrinkage and low-carbon grouting performance.
Patent Information
- Application Number
- CN202510055148.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-18
AI Technical Summary
The existing offshore wind grouting materials have high energy consumption and large carbon displacement, and the hydration and heat exothermic and shrinkage problems of silicate cement are difficult to solve, affecting the durability of grouting materials.
Solid waste-based gelling materials are used to replace silicate cement, and combined with ultra-high-active microsilicon powder, hollow microbeads and multi-stage composite sand, a high-strength and low-shrinkage gelling system is formed through the complex salt effect and the four-coordination isomerization effect of silicon.
It significantly reduces the carbon emissions of grouting materials, improves its strength, fluidity and durability, and meets the multiple performance requirements of offshore wind power basic grouting.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of industrial solid waste resource utilization and grouting material preparation, in particular to a high-performance solid waste-based offshore wind power grouting material and a preparation method thereof. Background Art
[0002] Wind energy has the characteristics of low cost, mature technology and high reliability. As a clean and renewable energy, it has attracted widespread attention from countries around the world. my country has abundant offshore wind energy resources. According to preliminary estimates, the exploitable offshore wind energy reserves are about 750GW, which has great development potential.
[0003] Grouting connection is a typical method of connecting offshore wind turbine foundations. Since grouting connections are subjected to multi-source, huge and continuous loads such as wind turbine operation, strong winds at sea, and wave impact, the stress state is more complex and extremely high technical indicators of grouting materials are required. The performance and quality of offshore wind power foundation grouting materials directly affect the efficiency and safety of engineering construction.
[0004] At present, the cementitious materials used in the grouting materials of my country's offshore wind power projects are basically cement, and the amount of cement used is large, accounting for more than 35% of the entire grouting material. Due to the "two grinding and one burning" process in the cement production process, a large amount of energy is consumed, and a large amount of CO2 is discharged at the same time, which makes the overall energy consumption of the grouting material large and the carbon emission high. In addition, silicate cement hydration releases a large amount of heat and shrinks greatly after hardening. For large-volume grouting, it requires late shrinkage compensation technology, which increases the technical difficulty of grouting material formula research. Once the expansion agent is used improperly, it will cause late strength loss or even expansion and cracking. Mg in seawater 2+ , Cl - 、SO4 2- After plasma invades the hardened silicate cement paste, it reacts with hydration products such as calcium hydroxide and calcium silicate hydrate (CSH) gel, destroying the originally stable structure and causing serious performance degradation. This poses a great challenge to the durability of offshore wind power grouting materials.
[0005] Solid waste-based cementitious materials are hydraulic cementitious materials made from one or more solid wastes such as water-quenched blast furnace slag, steel slag, desulfurized gypsum, fly ash, red mud, tailings, carbide slag, phosphogypsum, etc., processed and ground in a certain proportion. The silicon (aluminum) oxygen tetrahedron with potential hydraulic activity in water-quenched blast furnace slag is 2-3 times that of cement clinker. The mass proportion of divalent metal oxides (CaO, MgO, FeO) in steel slag accounts for more than 70%. They synergistically stimulate water-quenched blast furnace slag with desulfurized gypsum to produce "silicon tetracoordinate isomorphism effect" and "complex salt effect". While forming a large number of nano-diameter needle-rod-shaped complex salt crystals, a large number of nearly amorphous tightly packed hydrated calcium silicate gels and zeolite-like phases are also formed, and the needle-rod-shaped complex salt crystals are tightly wrapped, so that the entire cementitious system has good density, strength, volume stability and resistance to environmental erosion. The hydration reaction mechanism of solid waste-based cementitious materials is significantly different from that of silicate cement, which makes it have the unique properties of low hydration heat and ultra-low shrinkage. Using solid waste-based cementitious materials as binder materials to prepare offshore wind power grouting materials can realize the recycling of solid waste resources, promote the achievement of dual carbon goals, and produce good economic and social benefits. At the same time, solid waste-based cementitious materials themselves have the characteristics of high strength, low hydration heat, ultra-low shrinkage, and high durability. The prepared grouting material product has excellent performance, with the characteristics of large fluidity, micro expansion, no shrinkage, ultra-high strength, high elastic modulus, and high durability. Compared with ordinary cement-based offshore wind power grouting materials, it is a grouting material product with good comprehensive performance and more suitable for offshore wind power. Summary of the invention
[0006] The technical problem to be solved by the present invention is: in order to overcome the deficiencies in the prior art, a high-performance solid waste-based offshore wind power grouting material and a preparation method thereof are provided, the resulting product meets the various performance requirements required for offshore wind power foundation grouting, while utilizing a large amount of solid waste materials, the product has a small comprehensive carbon emission, meets low-carbon requirements, and has good economic and social benefits.
[0007] The technical solution adopted by the present invention is: a high-performance solid waste-based offshore wind power grouting material, including dry material and water, the weight percentage of the dry material is: solid waste-based cementitious material 40-45%, ultra-high active microsilica powder 2-5%, hollow microspheres 3-7%, multi-graded composite sand 50-55%, high-performance water reducer 0.2-0.5%, plastic expansion agent 0.03-0.1%, defoamer 0.05-0.2%; the mass ratio of water to dry material is (0.09-0.10): 1;
[0008] The total weight percentage of each substance in the solid waste-based cementitious material is: 55-65% of mineral powder, 15-20% of steel slag, 15-20% of desulfurized gypsum, 5-8% of lithium slag, and 1.0-1.5% of activity enhancer.
[0009] Furthermore, the performance of the mineral powder described in the present invention must meet the requirements of S95 mineral powder in the standard GB / T 18046-2017 "Granulated blast furnace slag powder for cement, mortar and concrete". According to a large number of experimental studies, the strength of solid waste-based cementitious materials also depends on the Al2O3 content in the mineral powder, so the Al2O3 content is required to be greater than or equal to 13%.
[0010] The silicon in the mineral powder exists mostly in the form of silicon-oxygen tetrahedron. The alkaline activator provides an alkaline environment to break the Si-O-Si bond in the silicon-oxygen tetrahedron to form -Si-OH and -Si-O-. In the alkaline environment, in addition to the destruction of the silicon-oxygen tetrahedron, the Ca-O and Mg-O in the mineral powder will also break, dissolving Ca 2+ Mg 2+ When the plasma enters the liquid phase, anions gather on the surface of the mineral powder. To maintain charge balance, H2O ionizes H + The anions -Si-O- accumulated on the surface of the mineral powder combine to form -Si-OH. As the hydration reaction proceeds, the aluminum-oxygen tetrahedron in the mineral powder is also destroyed to form -Al-OH. At this time, the Al2O3 in the mineral powder will also react to form H3AlO4 2- and Al(OH) 2+ As the mineral powder continues to hydrate, a large amount of H2SiO4 exists in the system. 2- 、HSiO4 3- and H3AlO4 2- In an alkaline environment, these ions and the Ca dissolved from the mineral powder itself 2+ and Ca in gypsum 2+ The combination generates CS-(A)-H and Aft.
[0011] Furthermore, the performance of the desulfurized gypsum of the present invention meets the requirements of desulfurized gypsum in the standard GB / T 21371-2019 "Industrial by-product gypsum used in cement". The Ca2+ released by the desulfurized gypsum when it is dissolved in water is 2+ and SO4 2- , directly participates in the hydration reaction to form calcium sulfate complex salt, and is the sulfate activator in the reaction system. The SO4 2- It is the key to maintaining the chemical reaction.
[0012] Furthermore, the steel slag of the present invention has the performance requirements of the first-class steel slag powder in the standard GB / T 20491-2017 "Steel slag powder for cement and concrete", and as a slow alkalinity providing component, its CaO+MgO content needs to be greater than 50%. The divalent metal oxides (CaO+MgO) in the steel slag are both the material basis for stimulating the slag to form CSH gel, and the material basis for capturing Al2O3 in the slag to form ettringite-type double salts with the participation of gypsum.
[0013] Furthermore, the lithium slag described in the present invention needs to meet the relevant requirements of YB / T 4230-2010 "Lithium slag powder used in cement and concrete", which is an industrial residue produced by producing lithium carbonate by a sulfuric acid method after calcining spodumene at a high temperature of 1,000 to 1,200°C. It contains a large amount of amorphous SiO2 and Al2O3, and the total content of the two must be greater than 60%. It is a highly active substance with a porous structure with a large internal surface area, which can react with a sulfate activator faster than mineral powder to form calcium sulfonate, and promote the hydrolysis of mineral powder as a precursor reaction.
[0014] Furthermore, the active enhancer described in the present invention is a mixture of sulphoaluminate cement clinker and sodium lactate in a mass ratio of 4:1. Sulphoaluminate cement clinker must meet the various requirements of SACC-I level in GB / T 37125-2018 "Sulphoaluminate Cement Clinker". It can react quickly in water to generate AFt fine crystals, provide nucleation sites for the subsequent synergistic reaction of mineral powder, steel slag and gypsum, and accelerate the early reaction. Sodium lactate, whose molecular formula is C3H5NaO3, has a bidentate ligand lactate anion produced by hydrolysis, which has a chelating effect and can form a water-soluble complex with the metal ions in the slag glass, destroying the glass structure, promoting the dissolution of the unreacted slag particles, generating more calcium sulfonate and CSH gel, optimizing the pore structure, and greatly enhancing the later strength.
[0015] Furthermore, the ultra-high activity microsilica powder described in the present invention is an amorphous, powdered silicon dioxide obtained by oxidizing silicon vapor discharged through the flue during the smelting of ferrosilicon and industrial silicon and collecting it in a specially designed dust collector. It is characterized by a SiO2 content of >90%, an average particle size of about 0.1um, and a specific surface area of >26000m 2 / kg, 28-day activity index>130%. Since the silicon powder particles are extremely fine, much smaller than other powder materials of the present invention, they can be filled in the gaps of large particles, playing the role of compacting the slurry and improving the gradation and particle size distribution of the slurry particles; at the same time, the highly active silicon dioxide can react with calcium hydroxide to generate amorphous hydrated calcium silicate gel, which can improve the interface state between the aggregate and the hardened slurry. In addition, the generated gel also has the effect of blocking the capillary channel, greatly reducing the connected pores and macropores of the hardened slurry, and further compacting the slurry, thereby improving the microstructure of the hardened slurry, which is manifested in a greatly increased strength and durability on a macro scale.
[0016] Furthermore, the hollow microspheres of the present invention are hollow microspheres containing gases such as nitrogen and carbon dioxide, which are separated, processed and purified from fly ash raw materials of coal-fired power plants by special processes. The main components are SiO2 and Al2O3. In addition, they also contain a small amount of CaO, TiO2, Fe2O3, etc. The characteristics are that most of the particle sizes are between 0.5 and 30 um, the particles smaller than 5 um exceed 20%, the water requirement ratio is 90%, the sphericity is greater than 85%, and the density is 0.5 to 0.8 g / cm 3 , high compressive strength. The particle size of hollow microspheres is between the above-mentioned silicon powder and solid waste-based cementitious materials. Due to their smooth and round particle shape, they can play a "ball" role in the slurry, greatly increasing the fluidity of the slurry; their low density and high compressive strength can reduce the bulk density of the hardened slurry, fill the internal pores, and thus improve the density and strength of the grouting material.
[0017] Furthermore, the multi-graded composite sand of the present invention is a sand obtained by combining quartz sand and gemstone sand in a certain proportion. The Mohs hardness of the quartz sand used is 7.0 and the density is 2.65 g / cm 3 The Mohs hardness of the pearl sand used is 7.0 and the density is 3.4g / cm 3 In order to obtain a dense skeleton structure and improve the performance of the grouting material, the present invention is based on the Modified Andreasen & Andersen close packing model:
[0018]
[0019] In the formula: P(D) is the screening pass rate of aggregate at a certain particle size D, %; Dmax is the maximum particle size of aggregate, mm; Dmin is the minimum particle size of aggregate, mm.
[0020] Combined with a large number of experimental tests, the bulk density of aggregate and the strength of grouting material were used as the evaluation criteria, and the q value was finally determined to be 0.25-0.30, and the weight percentage of the best aggregate gradation was obtained as follows:
[0021] 4 mesh-16 mesh: 44%-48%
[0022] 16 mesh-30 mesh: 16%-20%
[0023] 30 mesh-100 mesh: 25%-30%
[0024] 100 mesh-200 mesh: 8%-11%
[0025] At the same time, spherical bead sand is used to replace one of the particle size intervals in the above gradation, and quartz sand is used in the remaining intervals. The addition of this part of spherical bead sand can play the role of ball lubrication, greatly improving the fluidity of the grouting material.
[0026] Furthermore, the high-performance water reducer described in the present invention is a polycarboxylate water reducer (SD-600P-E powder polycarboxylate water reducer) with a water reduction rate of 35%. The polycarboxylate water reducer can be directional adsorbed on the surface of particles, so that the particles carry the same charge, forming electrostatic repulsion, thereby promoting the particles to disperse each other and release the water wrapped therein; the hydrophilic group in the water reducer has a strong polarity and can form a layer of stable solvated water film on the surface of the particles. This water film has a good lubrication effect, significantly reduces the sliding resistance between particles, and improves the fluidity of the grouting material.
[0027] Furthermore, the plastic expansion agent (EP-2 plastic expansion agent) described in the present invention comprises an azo compound, which reacts with water in an alkaline environment to produce fine bubbles mainly composed of nitrogen to achieve early volume expansion of the grouting material.
[0028] Furthermore, the defoamer described in the present invention is a powdered polyether-modified silicon defoamer (PW-03 powdered defoamer), which introduces a polyether chain into the polysiloxane chain through condensation technology, so that it has the advantages of both polyether and silicone defoamers. This defoamer can inhibit the formation of bubbles during the stirring process of adding water to the grouting material, and promote the rupture of bubbles after the stirring is completed, thereby reducing the gas content of the grouting material and enhancing the density.
[0029] A method for preparing a high-performance solid waste-based offshore wind power grouting material comprises the following steps:
[0030] A. Dry the dry material until the moisture content is less than 1%, weigh the raw materials in the dry material in proportion and mix them evenly, then put the dry material into an omnidirectional planetary ball mill for grinding, set the speed to 400r / min, the ball-to-material ratio to 7:1, and the grinding time to 30-90min, grind until the particle size of the solid waste-based gelling material is: D10 particle size 1.0-1.5μm, D25 particle size 2.5-3.5μm, D50 particle size 5.0-6.0μm, D90 particle size 18.0-20μm, D97 particle size 25.0-35.0μm, to obtain the solid waste-based gelling material;
[0031] The solid waste-based cementitious material described in the present invention can achieve the following strengths according to the relevant test methods of GB / T 17671-2021 "Test Method for Strength of Cement Mortar": 3-day compressive strength ≧40MPa, 28-day compressive strength ≧70MPa, 56-day compressive strength ≧80MPa; 3-day flexural strength ≧9MPa, 28-day flexural strength ≧12MPa, 56-day flexural strength ≧13MPa.
[0032] B. Weigh the mixed dry materials and water in A at a mass ratio of 1:(0.09-0.10);
[0033] C. Pour the mixed powder in B into the mixing equipment, start the mixing equipment and slowly add 90% of the water, continue stirring for 3-5 minutes until the slurry is uniform, then add the remaining water at one time, continue stirring for 2-3 minutes to obtain the grouting material.
[0034] Initial fluidity ≥330mm, 30min fluidity ≥320mm, and fluidity after 2 hours ≥290mm.
[0035] The compressive strength in 1 day is ≧60MPa, the compressive strength in 3 days is ≧100MPa, the compressive strength in 28 days is ≧160MPa, and the compressive strength in 56 days is ≧170MPa; the flexural strength in 1 day is ≧10MPa, the flexural strength in 3 days is ≧20MPa, the flexural strength in 28 days is ≧26MPa, and the flexural strength in 56 days is ≧27MPa.
[0036] The vertical expansion rate in 3 hours is 0.5% to 1.5%, the difference between the vertical expansion rate in 24 hours and 3 hours is 0.1% to 0.3%, and the self-shrinkage between 28 days and 1 day is 100×10-6 to 200×10-6.
[0037] The static elastic modulus after 28 days is greater than 55 GPa.
[0038] 28-day electric flux ≤200C, sulfuric acid corrosion test 150 dry-wet cycles compressive strength corrosion resistance coefficient ≥105%.
[0039] Compared with the prior art, the present invention has the following advantages:
[0040] 1. The present invention adopts solid waste-based cementitious materials to replace 525 silicate cement, which significantly reduces the carbon emissions of grouting products and reduces costs, which is conducive to the resource utilization of industrial solid waste. At the same time, the performance of the grouting material is significantly improved, and it has the advantages of ultra-high strength, elastic modulus, high fluidity, low shrinkage and high durability;
[0041] 2. The present invention is a hydration reaction with slag powder as the core, and steel slag and gypsum provide the alkalinity and SO4 required for the reaction. 2-Lithium slag provides a large amount of active SiO2 and Al2O3. Based on the double salt effect and the tetracoordinate isomorphism effect of silicon, various solid wastes are synergistically stimulated to form a large amount of needle-rod-shaped double salt calcium sulfonate, and a large amount of nearly amorphous CSH gel and zeolite phases are also formed. Since the solubility of this calcium sulfonate double salt is extremely low, it quickly reaches saturation in the solution after it is generated, and then precipitates. The concentration of various ions in the reactants is reduced, breaking the balance of the chemical reaction, providing a chemical driving force, and promoting the reaction. The needle-rod-shaped calcium sulfonate crystals in the hydration product overlap with each other and fill in the hydrated calcium silicate. At the same time, various unhydrated particles will also fill in the pores of the hydration product, reducing the internal pores, making the internal space more compact, forming a hydrated hardened body of the cementitious material, and improving the mechanical strength of the cementitious material;
[0042] 3. The present invention uses self-made high-strength solid waste-based cementitious materials as the cementing material, and simultaneously adds ultra-high active microsilica powder and hollow microspheres, and realizes excellent density, workability and hardening strength of cement paste through filling effect, morphological effect and synergistic excitation effect; through scientific design of aggregate grading, based on Modified Andreasen & Andersen close packing model, combined with a large number of experimental tests, the value of q is determined, so as to realize the most dense packing between aggregates, and at the same time, the quartz sand of some particle size ranges is replaced by the hardness, spherical and dense structure of the pearl sand, and the rolling effect of the pearl sand is used to greatly increase the fluidity of the grouting material; the fluidity, expansion and density of the grouting material are adjusted by adding high-performance polycarboxylic acid water reducer, defoamer and plastic expansion agent. Through the mutual cooperation of the above methods, the grouting material is finally realized with large fluidity, micro expansion, no shrinkage, ultra-high strength, high elastic modulus and high durability. DETAILED DESCRIPTION
[0043] The embodiments of the present invention are described in detail below. The embodiments are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operation processes are given, but the protection scope of the present invention is not limited to the following embodiments.
[0044] Example 1
[0045] A high-performance solid waste-based offshore wind power grouting material, comprising dry material and water, wherein the weight percentage of the dry material component is:
[0046] Solid waste-based cementitious material 43.5%, ultra-high activity microsilica powder 2.0%, hollow microspheres 4.0%, multi-graded composite sand 50.0%, high-performance water reducer 0.25%, plastic expansion agent 0.05%, and defoaming agent 0.2%.
[0047] The weight percentage of the raw materials of the solid waste-based cementitious material is: 57% of S95 mineral powder, 17% of desulfurized gypsum, 20% of steel slag, 5% of lithium slag, and 1.0% of active enhancer (sulfoaluminate cement clinker: sodium lactate = 4:1). All raw materials are dried to a moisture content of less than 1%, and the above raw materials are weighed in proportion and mixed evenly, and then all raw materials are put into an omnidirectional planetary ball mill for grinding, and the speed is set to 400r / min, the ball-to-material ratio is 7:1, and the grinding time is 75min. The particle size of the solid waste-based cementitious material is: D10 particle size 1.0-1.5μm, D25 particle size 2.5-3.5μm, D50 particle size 5.0-6.0μm, D90 particle size 18.0-20μm, and D97 particle size 25.0-35.0μm, so as to obtain the solid waste-based cementitious material.
[0048] The specific grading of multi-graded composite sand is: (4 mesh-16 mesh: 45%), (16 mesh-30 mesh: 18%), (30 mesh-100 mesh: 27%), (100 mesh-200 mesh: 10%), and the volume of Baozhu sand replaces half of the 30 mesh-100 mesh quartz sand.
[0049] A method for preparing a high-performance solid waste-based offshore wind power grouting material:
[0050] Weigh 9.5% of the dry material weight of tap water, pour the mixed dry material into the mixing equipment, start the mixing equipment and slowly add 90% of the water, continue stirring for 3min-5min until the slurry is uniform, then add the remaining water at one time, continue stirring for 2min-3min to obtain the grouting material.
[0051] Example 2
[0052] The weight percentage of dry material components is:
[0053] Solid waste-based cementitious materials 40.6%, ultra-high activity microsilica powder 3.0%, hollow microspheres 4.0%, multi-graded composite sand 52.0%, high-performance water reducer 0.25%, plastic expansion agent 0.05%, and defoaming agent 0.1%.
[0054] The weight percentage of the raw materials of the solid waste-based cementitious material is: 57% of S95 mineral powder, 17% of desulfurized gypsum, 20% of steel slag, 5% of lithium slag, and 1.0% of active enhancer (sulfoaluminate cement clinker: sodium lactate = 4:1). All raw materials are dried to a moisture content of less than 1%, and the above raw materials are weighed in proportion and mixed evenly, and then all raw materials are put into an omnidirectional planetary ball mill for grinding, and the speed is set to 400r / min, the ball-to-material ratio is 7:1, and the grinding time is 75min. The particle size of the solid waste-based cementitious material is: D10 particle size 1.0-1.5μm, D25 particle size 2.5-3.5μm, D50 particle size 5.0-6.0μm, D90 particle size 18.0-20μm, and D97 particle size 25.0-35.0μm, so as to obtain the solid waste-based cementitious material.
[0055] The specific grading of multi-graded composite sand is: (4 mesh-16 mesh: 45%), (16 mesh-30 mesh: 18%), (30 mesh-100 mesh: 27%), (100 mesh-200 mesh: 10%), and the volume of Baozhu sand replaces half of the 30 mesh-100 mesh quartz sand.
[0056] Weigh 9.5% of the weight of the dry material with tap water, and operate according to the preparation steps in Example 1 to prepare the grouting material of the present invention.
[0057] Example 3
[0058] The weight percentage of dry material components is:
[0059] Solid waste-based cementitious material 43.5%, ultra-high activity microsilica powder 2.0%, hollow microspheres 4.0%, multi-graded composite sand 50.0%, high-performance water reducer 0.25%, plastic expansion agent 0.05%, and defoaming agent 0.2%.
[0060] The weight percentage of the raw materials of the solid waste-based cementitious material is: 58.5% of S95 mineral powder, 15% of desulfurized gypsum, 18% of steel slag, 7% of lithium slag, and 1.5% of active enhancer (sulfoaluminate cement clinker: sodium lactate = 4:1). All raw materials are dried to a moisture content of less than 1%, and the above raw materials are weighed in proportion and mixed evenly, and then all raw materials are put into an omnidirectional planetary ball mill for grinding, and the speed is set to 400r / min, the ball-to-material ratio is 7:1, and the grinding time is 75min. The particle size of the solid waste-based cementitious material is: D10 particle size 1.0-1.5μm, D25 particle size 2.5-3.5μm, D50 particle size 5.0-6.0μm, D90 particle size 18.0-20μm, and D97 particle size 25.0-35.0μm, so as to obtain the solid waste-based cementitious material.
[0061] The specific grading of multi-graded composite sand is: (4 mesh-16 mesh: 45%), (16 mesh-30 mesh: 18%), (30 mesh-100 mesh: 27%), (100 mesh-200 mesh: 10%), and the volume of Baozhu sand replaces half of the 30 mesh-100 mesh quartz sand.
[0062] Weigh 9.5% of the weight of the dry material with tap water, and operate according to the preparation steps in Example 1 to prepare the grouting material of the present invention.
[0063] Example 4
[0064] The weight percentage of dry material components is:
[0065] Solid waste-based cementitious material 40.4%, ultra-high activity microsilica powder 4.0%, hollow microspheres 5.0%, multi-graded composite sand 50.0%, high-performance water reducer 0.2%, plastic expansion agent 0.05%, and defoaming agent 0.15%.
[0066] The weight percentage of the raw materials of the solid waste-based cementitious material is: 57% of S95 mineral powder, 17% of desulfurized gypsum, 20% of steel slag, 5% of lithium slag, and 1.0% of active enhancer (sulfoaluminate cement clinker: sodium lactate = 4:1). All raw materials are dried to a moisture content of less than 1%, and the above raw materials are weighed in proportion and mixed evenly, and then all raw materials are put into an omnidirectional planetary ball mill for grinding, and the speed is set to 400r / min, the ball-to-material ratio is 7:1, and the grinding time is 75min. The particle size of the solid waste-based cementitious material is: D10 particle size 1.0-1.5μm, D25 particle size 2.5-3.5μm, D50 particle size 5.0-6.0μm, D90 particle size 18.0-20μm, and D97 particle size 25.0-35.0μm, so as to obtain the solid waste-based cementitious material.
[0067] The specific grading of multi-graded composite sand is: (4 mesh-16 mesh: 44%), (16 mesh-30 mesh: 16%), (30 mesh-100 mesh: 29%), (100 mesh-200 mesh: 11%), and the volume of Baozhu sand replaces half of the 30 mesh-100 mesh quartz sand.
[0068] Weigh 10% of the weight of the dry material with tap water, and operate according to the preparation steps in Example 1 to prepare the grouting material of the present invention.
[0069] Comparative Example 1
[0070] The difference from Example 1 is that the solid waste-based cementitious material is completely replaced by 52.5 silicate cement commonly used on the market.
[0071] Comparative Example 2
[0072] The difference from Example 1 is that the weight percentage of the raw materials of the solid waste-based cementitious material is: S95 mineral powder 67%, desulfurized gypsum 12%, steel slag 10%, lithium slag 10%, and activity enhancer 1.0% (sulfoaluminate cement clinker: sodium lactate = 4:1).
[0073] Comparative Example 3
[0074] The difference from Example 1 is that the weight percentages of the raw materials of the solid waste-based cementitious material are: 58% S95 mineral powder, 17% desulfurized gypsum, 20% steel slag, and 5% lithium slag.
[0075] Comparative Example 4
[0076] The difference from Example 1 is that the hollow microspheres are completely replaced by ordinary first-grade fly ash, and the quartz sand is not partially replaced by the pearl sand.
[0077] Comparative Example 5
[0078] The difference from Example 1 is that ultra-high activity microsilica powder is not added, and this part of the mass is added to the S95 mineral powder.
[0079] Detailed performance tests were conducted on the above-mentioned Examples 1, 2, 3, 4 and Comparative Examples 1, 2, 3, 4, and 5, wherein the test methods for mortar fluidity and vertical expansion rate refer to GB / T50448-2015 "Technical Specifications for Application of Cement-based Grouting Materials", the test methods for compressive strength and flexural strength refer to GB / T17671-2021 "Test Method for Cement Mortar Strength (ISO Method)", the test method for static elastic modulus refers to GB / T50081-2019 "Standard Test Method for Mechanical Properties of Ordinary Concrete", and the test methods for electric flux, sulfate corrosion resistance, and shrinkage refer to GB / T50082-2009 "Standard Test Method for Long-term Performance and Durability of Ordinary Concrete". The specific test results are shown in Table 1.
[0080] Table 1 Experimental results of examples and comparative examples
[0081]
[0082] As can be seen from the above table, Examples 1, 2, 3, and 4 vary within the reasonable ratio range of the present invention, and the grouting material prepared according to the given preparation method has excellent performance and meets the following performances: 1. Initial fluidity ≧330mm, 30min fluidity ≧320mm, and fluidity ≧290mm after 2 hours. 2. 1-day compressive strength ≧60MPa, 3-day compressive strength ≧100MPa, 28-day compressive strength ≧160MPa, and 56-day compressive strength ≧170MPa; 1-day flexural strength ≧10MPa, 3-day flexural strength ≧20MPa, 28-day flexural strength ≧26MPa, and 56-day flexural strength ≧27MPa. 3. The vertical expansion rate in 3 hours is 0.5% to 1.5%, the difference between the vertical expansion rate in 24 hours and 3 hours is 0.1% to 0.3%, and the self-shrinkage between 28 days and 1 day is 100×10-6 to 200×10-6. 4. The static elastic modulus in 28 days is greater than 55GPa. 5. The electric flux in 28 days is ≤200C, and the corrosion resistance coefficient of compressive strength after 150 dry-wet cycles of sulfuric acid corrosion test is ≥105%.
[0083] Comparative Example 1 shows that for the grouting material of the present invention, the use of high-strength solid waste-based cementitious material has better performance in all aspects than 525 silicate cement. The solid waste-based cementitious material has a hardened structure formed by a large number of needle-shaped calcium aluminate crystals that are interlaced and interwoven with each other with amorphous CS-(A)-H, and has higher strength and stability.
[0084] Comparative Example 2 shows that steel slag and gypsum in the solid waste-based cementitious material of the present invention are important alkalinity and sulfate activators, which have a significant impact on the rate and degree of hydration reaction. Inappropriate dosage will cause a significant decrease in performance.
[0085] Comparative Example 3 shows that the activity enhancer of the present invention has a significant effect on enhancing the activity of solid waste-based cementitious materials, and its nucleation effect and the effect of promoting the dissolution of mineral powder particles are critical to the early and late strength development of the material.
[0086] Comparative Example 4 shows that the rolling action of the hollow microspheres and gem sand of the present invention has a great influence on the fluidity of the grouting material. The hollow microspheres and gem sand act as spherical rolling balls between micron-sized powders and millimeter-sized aggregates, respectively, which greatly reduces the friction between the particles of the grouting material, and the macroscopic performance is excellent fluidity.
[0087] Comparative Example 5 shows that the extremely small particles of the ultra-high activity microsilica powder of the present invention fill the voids in the grouting material. At the same time, its high activity promotes the hydration of the mineral powder to generate more CS-(A)-H gel, greatly reducing the porosity and pore size of the hardened slurry, enhancing the density, and thus improving the strength of the grouting material.
[0088] The various raw materials used in the grouting material described in the present invention are all selected through a large number of experiments and are based on scientific principles. The multi-graded composite sand constructs a high-strength skeleton structure, and the solid waste-based cementitious material acts as a cementing material. The strength and stability of the system are greatly enhanced through the complex salt effect and the silicon four-coordination isomorphism effect. The ultra-high active microsilica powder, hollow microbeads and gem sand further adjust the workability, mechanical strength and durability of the grouting material through the filling effect, morphological effect and composite gelling effect. Various admixtures are compounded to adjust the fluidity, expansibility and density of the grouting material, and finally an offshore wind power grouting material with large fluidity, micro-expansion, low shrinkage, ultra-high strength, high elastic modulus and excellent durability is obtained.
Claims
1. A high-performance solid waste-based offshore wind power grouting material, characterized by: The invention comprises dry material and water, wherein the weight percentage of the dry material is: 40-45% of solid waste-based cementitious material, 2-5% of ultra-high active microsilica powder, 3-7% of hollow microspheres, 50-55% of multi-graded composite sand, 0.2-0.5% of high-performance water reducing agent, 0.03-0.1% of plastic expansion agent, and 0.05-0.2% of defoaming agent; the mass ratio of water to dry material is (0.09-0.10):1; The total weight percentage of each substance in the solid waste-based cementitious material is: 55-65% of mineral powder, 15-20% of steel slag, 15-20% of desulfurized gypsum, 5-8% of lithium slag, and 1.0-1.5% of activity enhancer.
2. A high-performance solid waste-based offshore wind power grouting material according to claim 1, characterized in that: The mineral powder is S95 grade granulated blast furnace slag powder, and the Al2O3 content contained in the mineral powder must be greater than or equal to 13%.
3. A high-performance solid waste-based offshore wind power grouting material according to claim 1, characterized in that: The desulfurized gypsum is dissolved in water and the Ca2+ released 2+ and SO4 2- , directly participate in the hydration reaction to form calcium aluminate complex salt.
4. A high-performance solid waste-based offshore wind power grouting material according to claim 1, characterized in that: The content of CaO and MgO in the steel slag is greater than 50%.
5. A high-performance solid waste-based offshore wind power grouting material according to claim 1, characterized in that: The lithium slag is industrial residue produced by calcining spodumene at a high temperature of 1000-1200°C and then producing lithium carbonate by sulfuric acid method. The total content of SiO2 and Al2O3 in the lithium slag is greater than 60%, and the lithium slag has a porous structure.
6. A high-performance solid waste-based offshore wind power grouting material according to claim 1, characterized in that: The activity enhancer is a mixture of sulphoaluminate cement clinker and sodium lactate in a mass ratio of 4:
1.
7. A high-performance solid waste-based offshore wind power grouting material according to claim 1, characterized in that: The ultra-high active microsilica powder is an amorphous, powdered silicon dioxide collected after the silicon vapor discharged through the flue is oxidized during the smelting of ferrosilicon and industrial silicon. The SiO2 content is greater than 90%, the average particle size is 0.1um, and the specific surface area is greater than 26000m 2 / kg, and the activity index at 28 days was greater than 130%.
8. A high-performance solid waste-based offshore wind power grouting material according to claim 1, characterized in that: The hollow microspheres are hollow microspheres containing nitrogen and carbon dioxide gases, separated, processed and purified from fly ash raw materials of coal-fired power plants. The components include SiO2 and Al2O3, with a particle size of 0.5-30um, a sphericity greater than 85%, and a density of 0.5-0.8g / cm3.
9. A method for preparing a high-performance solid waste-based offshore wind power grouting material for use in any one of claims 1 to 8, characterized in that: The following steps are involved: A. Dry the dry material until the moisture content is less than 1%, weigh the raw materials in the dry material in proportion and mix them evenly, then put the dry material into an omnidirectional planetary ball mill for grinding, set the speed to 400r / min, the ball-to-material ratio to 7:1, and the grinding time to 30-90min, grind until the particle size of the solid waste-based gelling material is: D10 particle size 1.0-1.5μm, D25 particle size 2.5-3.5μm, D50 particle size 5.0-6.0μm, D90 particle size 18.0-20μm, D97 particle size 25.0-35.0μm, to obtain the solid waste-based gelling material; B. Weigh the mixed dry materials and water in A at a mass ratio of 1:(0.09-0.10); C. Pour the mixed dry materials in B into the mixing equipment, start the mixing equipment and slowly add 90% of the water, continue stirring for 3-5 minutes until the slurry is uniform, then add the remaining water at one time, continue stirring for 2-3 minutes to obtain the grouting material.
Citation Information
Cited By
Gluing agent for cemented filling of argillaceous tailings and use method of cementing agent
CN120309281A
A geofixing agent for clayey tailings cemented filling and a method of using the same
CN120309281B
Quick-drying cement-based repair mortar and preparation method thereof
CN120794541A
Energy storage battery box based on light high-performance concrete and preparation method of energy storage battery box
CN120864846A
Super-early-strength all-solid waste cementing material and preparation method thereof
CN120887701A